Fractured Souls and Hyper-Tension Elite Fragmentation in Traumatised Societies - Schiefer, U. (Dinâmicas destrutivas da cooperação para a educação: turbulências e ressonâncias IIICOOPEDU, 2016)
In most societies, education, in all its forms, plays a significant role in the formation and reproduction of the elites. In traumatised African societies the elite formation is influenced by accelerated transitions from agrarian to urbanised societies under war conditions which, in many cases, reproduce very high levels of social tensions. The collective education approach in post-war rural societies, even in its modern form, as formal low level schooling, is supplanted by a multiplicity of individual based education models transported and implanted by a multi-level approach of international state and non-state actors. International cooperation in education, strictu sensu, in many societies has not delivered on its promises. To understand the impacts, it is useful to consider all forms of international cooperation which operate on the elite formation on many levels, visible and less visible, formalized and non-formalised and not only in the sector of formal education.